Analyse des liens de la typicité catégorielle des élèves avec la quantité et qualité des interactions en classe - Lara Laflotte (Nantes Université, 2018)
This text aims to assess student categories in teachers' cognitions as well as the effects of students' closeness to these mental categories on classroom interactions. Two studies are conducted in the canton of Geneva with primary school teachers and their class. Study 1 invites twenty-three teachers to perform three tasks of student categorization. Eight study-1-teachers participated to study 2. In that study, teachers are observed and filmed during teaching to assess classroom interactions in relation to students' categorizations and categorical closeness. Study 1's results verify the existence of three to five students' categories depending on the used research method and show the presence of prototypical students within these categories. Study 2 shows five types of classroom interactions identified through factor analysis. Regression analysis demonstrate that the students' categorical typicity has a weak impact on student-teacher classroom interactions. These observations rise questions about teacher training and allow different research perspectives.